1993
DOI: 10.1073/pnas.90.22.10793
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of glycoprotein D cDNA, which encodes the major subunit of the Duffy blood group system and the receptor for the Plasmodium vivax malaria parasite.

Abstract: ABSTRACTcDNA clones encoding the major subunit of the Duffy blood group were isolated from a human bone marrow cDNA library using a PCR-amplifled DNA anti-Duffy murine monoclonal antibody reacted with a synthetic peptide deduced from the cDNA clone. Hydropathy analysis suggested the presence of9 membrane-spanning a-helices. In bone marrow RNA blot analysis, the gpD cDNA detected.a 1.27-kb mRNA in Duffy-positive but not in Duffynegative individuals. It also identified the same size mRNA in adult kidney, adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
157
0
3

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(163 citation statements)
references
References 27 publications
1
157
0
3
Order By: Relevance
“…Therefore, we explored the possibility of using a type I transmembrane protein in the construction of RhD fusion proteins. Fy protein, a blood group antigen and a promiscuous chemokine receptor, has been expressed on the surface of K562 cells that does not have detectable background (18,20). The extracellularly located N-terminal domain (64 residues) of the protein is recognized by anti-Fy6.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we explored the possibility of using a type I transmembrane protein in the construction of RhD fusion proteins. Fy protein, a blood group antigen and a promiscuous chemokine receptor, has been expressed on the surface of K562 cells that does not have detectable background (18,20). The extracellularly located N-terminal domain (64 residues) of the protein is recognized by anti-Fy6.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find any significant difference in the proliferation and invasion potential, comparing the DARC-transfected cells with the mocktranfected cells or wild-type MDA-MB-435HM, which indicating that the enhanced expression of DARC had no remarkable influence on the intracellular signaling pathway associated with the tumor cells proliferation and invasion in vitro. It has been reported that DARC gene modification has no influence in cell growth characteristics in vitro, except for their acquired chemokine-binding capacity in human erythroleukemic cell line K562 (Chaudhuri et al, 1994) as well as in human pulmonary cancer cell A549 (Addison et al, 2004). DARC gene expression appears to effect in vivo growth and has no effect on in vitro growth.…”
Section: Inhibition Of Breast Cancer Growth and Metastasis By Darcmentioning
confidence: 99%
“…Another possible IL-8 receptor, the Duffy antigen, was originally identified as a blood group antigen required for invasion by the malarial parasites, Plasmodium vivax and Plasmodium knowlesi (71)(72)(73). Further studies revealed that a chemokinebinding protein expressed on red blood cells is identical to the Duffy antigen, which was subsequently renamed Duffy antigen receptor for chemokines (DARC) (74).…”
Section: Fig 5 Il-8 Is a Potent Chemoattractant For Himec Migrationmentioning
confidence: 99%